Aplikasi ORCA Algorithm Pada Optimasi Penyediaan Daya Sistem Berbasis Mobilitas Kendaraan Listrik - A.N. Afandi; Farrel Candra W.A; Machrus Ali (Universitas Darul Ulum, 2023)
In reality, the electric power system is run by combining several production units to commit to meeting changes in load demand at each operating time. Apart from that, it also takes into account efforts to reduce overall costs while maintaining the specified technical limits. The general thing that is often done to achieve this condition is carried out with an economical operational approach which leads to minimizing operational costs. During 24 hour operations, the model that is often used is Dynamic Economic Operation (DEO) which takes into account changes in load demand over a 24 hour seven day period. This study uses the IEEE-62 bus system as a model, which is optimized using the Orca Algorithm. The load flexibility pattern is based on the effect of charging integration for Electric Vehicles (EV). The simulation results show that the Orca algorithm solves problems with fast iteration and provides the best results. The Orca algorithm provides good levels of convergence, power output and overall operational costs. EV distances and routes also have varying driving characteristics and varying power utilization. In terms of travel modes, which include one way and two trips, it has a mobility of 208,000 EVs, with respective distributions for working/business/study, service/shopping, leisure time, and other purposes.